Neonatal Assessment Manual Score: Is There a Role of a Novel, Structured Touch-Based Evaluation in Neonatal Intensive Care Unit? - Manzotti, Andrea; Cerritelli, Francesco; Chiera, Marco; Lombardi, Erica; La Rocca, Simona; Biasi, Pamela; Galli, Matteo; Esteves, Jorge; Lista, Gianluca (Frontiers in Pediatrics, 2020)
Despite the technological improvements in monitoring preterm infants in the neonatal intensive care unit, routine-care in the neonatal ward is primarily based on manual procedures. Although manual clinical procedures play a critical role in neonatology, little attention has been paid to palpation as a clinical assessment tool. Palpation is a clinical evaluation tool that relies mostly on the senses of touch and proprioception. Based on recent studies investigating the role and clinical effectiveness of touch in full-term and preterm babies, this paper proposes an evaluative touch-based procedure – the Neonatal Assessment Manual scorE (NAME) model – that could be useful in the neonatal ward and describes its rationale. The operator applies gentle light pressures to the infant’s body tissues. In essence, the touch stimulates low-threshold afferent fibers that could influence the interoceptive cerebral network and the autonomic nervous system, thus altering the blood flow and breathing rhythm. These events could change how bodily fluids distribute among body segments, and hence the body volume. The volume modification could be felt manually through haptic perception due to the high sensitivity of the fingers. Based on their clinical conditions and stage of development, infants will respond differently to the applied pressures. Evaluating the infant’s response, the operator produces a score of “Bad”, “Marginal”, or “Good” for communicating quickly and clearly the infant’s conditions to other professionals. Since the NAME model is intended for every professional used to touch-based procedures, if future studies confirmed its validity and reliability in clinical practice, the NAME model could become a part of the neonatal ward routine-care for better assessing and managing the infant’s conditions, even during emergencies.